2003
DOI: 10.1172/jci17856
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow stem cells contribute to repair of the ischemically injured renal tubule

Abstract: The paradigm for recovery of the renal tubule from acute tubular necrosis is that surviving cells from the areas bordering the injury must migrate into the regions of tubular denudation and proliferate to re-establish the normal tubular epithelium. However, therapies aimed at stimulating these events have failed to alter the course of acute renal failure in human trials. In the present study, we demonstrate that Lin -Sca-1 + cells from the adult mouse bone marrow are mobilized into the circulation by transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
299
3
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 472 publications
(326 citation statements)
references
References 29 publications
17
299
3
7
Order By: Relevance
“…In this regard, exogenous cytokine-induced mobilization of BMCs has been shown to be beneficial after stroke as well as MI [6,28]. Moreover, the identification of BMC-derived cells in various injured tissues, including brain, liver, kidney, lung, and heart, indicates that tissue injury can induce mobilization of BMCs from the marrow into the PB [1][2][3][4][5]7,8]. However, the mobilization of pluripotent stem cells after acute MI has never been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, exogenous cytokine-induced mobilization of BMCs has been shown to be beneficial after stroke as well as MI [6,28]. Moreover, the identification of BMC-derived cells in various injured tissues, including brain, liver, kidney, lung, and heart, indicates that tissue injury can induce mobilization of BMCs from the marrow into the PB [1][2][3][4][5]7,8]. However, the mobilization of pluripotent stem cells after acute MI has never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…BM-derived cells (BMCs) have been shown to participate in tissue repair following injury to several organs, including the brain, liver, lung, kidney [1][2][3][4][5] as well as the heart [6][7][8][9][10][11]. Cardiomyocytes derived from BMCs have been noted in the heart after myocardial infarction (MI) [6,7,10].…”
Section: Introductionmentioning
confidence: 99%
“…97,98 This mechanism had been proposed for heart infarct, 39,99 stroke, 100,101 liver damage, 102 kidney damage, 43,103 pancreatic damage, 104 skeletal muscle injury, 105 bone fractures 106 and lung damage. 107 Accordingly, during these various organ/tissue injury models, there were circulating cells identified in PB that express markers for endothelial-, mesenchymal-, cardiac-, skeletal muscle-, liver-, kidney, neural-and bone-NSC.…”
Section: Concept Of Circulation Of Cxcr4 þ Non-hematopoietic Nscmentioning
confidence: 99%
“…Several investigators in the past few years have demonstrated that BM-derived cells can contribute to the regeneration of nonhematopoietic organs and tissues (Jackson et al, 2001;Orlic et al, 2001;Corbel et al, 2003;Kale et al, 2003). These observations were mainly explained by the hypothesis that HSC are "plastic" and, thus, could trans-dedifferentiate into stem cells committed for various organs and tissues (Mezey et al, 2000;Corti et al, 2002b).…”
Section: Bm-derived Stem Cells and Tissue/organ Regeneration: Evidencmentioning
confidence: 99%
“…HSC and other nonhematopoietic stem cells are actively chemoattracted by factors secreted by BM stroma cells and osteoblasts (e.g., stromal derived factor-1 [SDF-1] and hepatocyte growth factor [HGF]) and colonize marrow by the end of the second and the beginning of the third trimester of gestation (Kmiecik et al, 1992;Ma et al, 1998;Nagasawa, 2000;Taichman et al, 2001). Accumulating evidence suggests that these nonhematopoietic stem cells residing in the BM play some role in the homeostasis/turnover of peripheral tissues and if needed could be released/mobilized from the BM into circulation during tissue injury and stress, thus facilitating the regeneration of damaged organs (LaBarge and Blau, 2002;Kale et al, 2003;Kollet et al, 2003;Abbott et al, 2004;Kucia et al, 2004Kucia et al, , 2006cWojakowski et al, 2004;Long et al, 2005;Gomperts et al, 2006). It is also possible that, in steady state conditions, they shuttle at very low level between BM and stem cell niches in peripheral organs/tissues.…”
Section: Introductionmentioning
confidence: 99%